2010
DOI: 10.1007/s10508-010-9701-5
|View full text |Cite
|
Sign up to set email alerts
|

Postnatal Testosterone Levels and Temperament in Early Infancy

Abstract: Recent research showing associations between behavior and postnatal testosterone levels in male infants has suggested that the transient activation of the hypothalamic-pituitary-gonadal axis in early infancy may influence the expression of gender phenotypes in later development (i.e., the postnatal hormone hypothesis). As a further test of the relationship between postnatal hormones and behavior in infancy, we measured digit ratios and salivary testosterone in 76 male and female infants (3-4 months of age) and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 28 publications
(18 citation statements)
references
References 45 publications
0
18
0
Order By: Relevance
“…Previous studies have reported significantly higher rates of childhood problem externalizing and internalizing behaviors associated with prenatal testosterone exposure. However, these studies have been limited by population selection [3], small sample sizes [6], [8] or single point outcome measures [10], [11] [8]. In contrast, our study uses data from four time points from age two to ten years from a relatively large population-based cohort.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies have reported significantly higher rates of childhood problem externalizing and internalizing behaviors associated with prenatal testosterone exposure. However, these studies have been limited by population selection [3], small sample sizes [6], [8] or single point outcome measures [10], [11] [8]. In contrast, our study uses data from four time points from age two to ten years from a relatively large population-based cohort.…”
Section: Discussionmentioning
confidence: 99%
“…With regard to internalizing outcomes, exposure to higher levels of intrauterine testosterone was found to lead to increased fear reactivity, determined by the child’s reaction to an unfamiliar robotic toy, in infant boys but not in girls [10]. Higher salivary testosterone levels in male infants measured postnatally have also predicted increased negative affectivity, such as sadness, distress, and fear [11]. Conversely, exposure to lower levels of testosterone has been associated with an increase in emotional symptoms in boys in mid-childhood [8].…”
Section: Introductionmentioning
confidence: 97%
“…Postnatal testosterone levels have been correlated with decreased language development (62), decreased value to social stimuli (61,63), increased activity levels (64,65) and increased negative affectivity (66). Decreased language development has been demonstrated through associations with increased testosterone levels and both decreased phoneme discrimination (62) and lower ver balization at 18 months of age (67).…”
Section: Behavioral Manifestations Of Increased Androgens In Term Infmentioning
confidence: 99%
“…Although levels of free testosterone in infancy are much lower than that in adulthood (de Ronde et al, 2005;Huhtaniemi et al, 1986), the postnatal increase in testosterone levels is critical for the normal development of male genitalia (Main et al, 2005) and higher postnatal salivary testosterone in boys predicts greater male-typical visual interests during early infancy (Alexander et al, 2009a). Significantly, the hypothesis that androgens levels in the early postnatal period may contribute to the organization of sex-linked behavior in humans (Alexander and Saenz, 2011;Alexander et al, 2009a) is supported by recent findings that postnatal urinary testosterone levels are associated with greater male-typical play behavior and less female-typical play behavior in girls and boys, respectively, at 14-months of age (Lamminmaki et al, 2012).…”
Section: Introductionmentioning
confidence: 99%